2009
DOI: 10.1124/jpet.108.148627
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Nucleus Accumbens as a Neural Substrate of Heroin-Induced Immune Alterations

Abstract: Administration of opioid drugs such as heroin produces several immunosuppressive effects, including decreases in natural killer (NK) cell activity, lymphocyte proliferative responses, and nitric oxide production. Interestingly, opioids have been shown to alter many immune parameters indirectly by modulating the immunoregulatory actions of the central nervous system. Recently, it has been demonstrated that morphine inhibits NK cell activity through a neural pathway that requires the activation of dopamine D 1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
3
18
0
1
Order By: Relevance
“…We show that activation of the reward system increases the primary antibacterial immune response, as well as the immune response after pathogen re-exposure. These findings are in line with pharmacological and lesion studies that implicate the reward system in immune activity 28,29 . On the basis of our data, we speculate that this rewardsystem-driven enhancement of antibacterial immunity might be beneficial in natural contexts that are known to activate the VTA but which might also increase the likelihood of exposure to pathogens (such as feeding or mating behaviors) 30,31 .…”
Section: -5 and Supplementarysupporting
confidence: 90%
“…We show that activation of the reward system increases the primary antibacterial immune response, as well as the immune response after pathogen re-exposure. These findings are in line with pharmacological and lesion studies that implicate the reward system in immune activity 28,29 . On the basis of our data, we speculate that this rewardsystem-driven enhancement of antibacterial immunity might be beneficial in natural contexts that are known to activate the VTA but which might also increase the likelihood of exposure to pathogens (such as feeding or mating behaviors) 30,31 .…”
Section: -5 and Supplementarysupporting
confidence: 90%
“…Taken together, these data indicate that morphine is immunosuppressive within the periphery, but that neonatal handling does not program baseline IL-10 expression within the peripheral immune system as it does within the brain. Rather, we hypothesize that the difference in peripheral immunosuppression following morphine administration between handled and non-handled control rats is driven by the differential glial response within the NAcc as it has been reported that the NAcc is necessary for the peripheral immunosuppression induced by morphine (Saurer et al, 2008; Saurer et al, 2009). …”
Section: Resultsmentioning
confidence: 90%
“…Both direct (i.e., neuronal) and indirect (i.e., through the peripheral immune cells) mechanisms are involved in the opioid-induced immunosuppression and neuroimmunomodulation (Sacerdote 2008;Saurer et al 2009). Heroin has been shown to increase dopamine release in rat nucleus accumbens shell, which in turn has been linked with the immunosuppressive NK cell activity reduction in the periphery, thus demonstrating a true neuroimmune modulation by opioids (Saurer et al 2009). …”
Section: Hcv Treatmentmentioning
confidence: 99%